NTCP modeling analysis of acute hematologic toxicity in whole pelvic radiation therapy for gynecologic malignancies – A dosimetric comparison of IMRT and spot-scanning proton therapy (SSPT). Issue 9 (September 2016) - Yoshimura, Takaaki; Kinoshita, Rumiko; Onodera, Shunsuke; Toramatsu, Chie; Suzuki, Ryusuke; Ito, Yoichi M.; Takao, Seishin; Matsuura, Taeko; Matsuzaki, Yuka; Umegaki, Kikuo; Shirato, Hiroki; Shimizu, Shinichi
Highlights: This dosimetric study includes 13 postoperative gynecological malignancy patients. Spot-scanning proton therapy (SSPT) was compared to IMRT in whole pelvic radiotherapy. The dose to the bone marrow and the risk of hematologic toxicity (HT) were compared. Bone marrow dose using SSPT were significantly lower than IMRT (p = 0.0002). NTCP value for the risk of HT using SSPT was significantly lower than IMRT (p = 0.0002). Abstract: Purpose: This treatment planning study was conducted to determine whether spot scanning proton beam therapy (SSPT) reduces the risk of grade ⩾3 hematologic toxicity (HT3+) compared with intensity modulated radiation therapy (IMRT) for postoperative whole pelvic radiation therapy (WPRT). Methods and materials: The normal tissue complication probability (NTCP) of the risk of HT3+ was used as an in silico surrogate marker in this analysis. IMRT and SSPT plans were created for 13 gynecologic malignancy patients who had received hysterectomies. The IMRT plans were generated using the 7-fields step and shoot technique. The SSPT plans were generated using anterior-posterior field with single field optimization. Using the relative biological effectives (RBE) value of 1.0 for IMRT and 1.1 for SSPT, the prescribed dose was 45 Gy(RBE) in 1.8 Gy(RBE) per fractions for 95% of the planning target volume (PTV). The homogeneity index (HI) and the conformity index (CI) of the PTV were also compared. Results: The bone marrow (BM) and femoral head doses using SSPT were significantly lower than with IMRT. The NTCP modeling analysis showed that the risk of HT3+ using SSPT was significantly lower than with IMRT (NTCP = 0.04 ± 0.01 and 0.19 ± 0.03, p = 0.0002, respectively). There were no significant differences in the CI and HI of the PTV between IMRT and SSPT (CI = 0.97 ± 0.01 and 0.96 ± 0.02, p = 0.3177, and HI = 1.24 ± 0.11 and 1.27 ± 0.05, p = 0.8473, respectively). Conclusion: The SSPT achieves significant reductions in the dose to BM without compromising target coverage, compared with IMRT. The NTCP value for HT3+ in SSPT was significantly lower than in IMRT.